Cost-Benefit analysis of rehabilitation approaches for water distribution networks - M. Farouk, Abdelrahman; Noor Suraya, Romali; Rahimi, A. Rahman (AIP Publishing, 2023)
Nowadays, it is crucial to have sustainability; water sustainability is one of the sustainable development goals. However, many threats face water sustainability. One of the challenges towards reaching water sustainability is represented in the high levels of non-revenue water (NRW) that faces many countries. As a step towards reducing NRW and reaching water sustainability, this paper aims to identify the cost-effective water distribution network (WDN) rehabilitation approaches. First, WDN rehabilitation approaches were identified from a systematic review. Then, the identified WDN rehabilitation approaches were used in the development of the questionnaire survey. 176 valid responses were collected, the collected data was analyzed using mean score ranking, normalization, and cost-benefit analysis. The results of the data analysis showed that the cost-effective approaches are; Pipe bursting, Compact pipe, Pipe ramming, Trenchless, Supervisory control and data acquisition (SCADA), cured-in-place pipe (CIPP), Zoning network, and Slip lining. The findings can be a valuable reference for the water industry in the WDN rehabilitation process. Further analysis and development are required to get rid of each approach's limitations. Reducing NRW is regarded as a top solution towards having water sustainability suitable development.